Za‘ba dan Pendapatan Perbahasannya tentang Takdir - Ahmad Nabil Amir; Tasnim Abdul Rahman (Jurnal Intelek Insan Cendikia, 2024)
The paper discusses the theological work of Zainal Abidin bin Ahmad, or his acronym Za‘ba, i.e., Falsafah Takdir (The Philosophy of Predestination) that underlie his rational outlook of Islamic theological and discursive tradition. Such understanding was derived from the practical viewpoint espoused by Dr. Basharat Ahmad in his article published in Islamic Review (August-September 1921) entitled “Taqdir (Pre-Measurement) in Islam” that articulated coherent religious viewpoint of predestination that reflected its rational foundation and reassuring and logical spirit. Za‘ba tried to encapsulate the ideas in the context of the Malay community to bring forth its encouraging and dynamic perspective aspiring to reform their pessimistic religious views and understanding and fatalistic attitude of Islamic faith. The study is based on qualitative method in the form of library and documentary survey. It uses normative, descriptive and historical approaches to analyze the data and reach final conclusion. The finding shows that Za‘ba embodies the enlightening spirit of Islam aligned with the classical school of rational and speculative thought, which aimed to bring new consciousness into the Malay community through his reinterpretation of the traditional concept of predestination, in light of new metaphysical perspective that brings inspiring philosophical dimension of its dynamic ethical and religious postulate and its implication in modern context to realize the ideal of reform and its promising intellectual and religious aspiration.